A Reforma Luterana e suas influências no Rio Grande do Sul - (:unkn) unknown (Universidade Federal do Pampa, 2024)
The general objective of this work is to study the Lutheran reform, emphasizing the collaborations brought by German immigrants to the formation of the culture of the state of Rio Grande do Sul. The Lutheran Reformation was initiated by the monk Martinho Luther in the 16th century, in the year 1517, in Germany. Martin Luther was a monk of the Catholic Church and saw the teachings practiced by it as erroneous. From a very early age, Luther received a strict education, however, this education that Luther received influenced the church reform movement as well as the changes that the reformer considered necessary for society to understand the meaning and need for the Reformation. This research is bibliographic and documentary, with a qualitative approach. We seek to present as results what were the main changes promoted by the Lutheran Reformation and its theological, social and political influences, focusing on changes in Christian doctrine, ecclesiastical structure, and the relationship between religion and State, in addition to analyzing how these transformations modified the Brazilian and southern Brazilian culture, contributing to the spread of Protestantism to the present day.
The Lutheran Reformation and its influences in Rio Grande do Sul
Keywords: Reforma Luterana; Mudanças na educação; História; Lutheran Reformation; Changes in education; History; Rio Grande do Sul -Reforma Luterana; Rio Grande do Sul - Lutheran Reformation; CIENCIAS HUMANAS